Development of a semiempirical potential for simulations of thiol-gold interfaces. Application to thiol-protected gold nanoparticles - Olmos Asar, Jimena Anahí (2011)
A new semiempirical potential, based on density functional calculations and a bond-order Morse-like potential, is developed to simulate the adsorption behavior of thiolate molecules on non-planar gold surfaces, including relaxing effects, in a more realistic way. The potential functions include as variables the metal-molecule separation, vibrational frequencies, bending and torsion angles between several pairs of atom types and the coordination number of both the metal (Au) and thiolate groups. The potential was parameterized based on a set of density functional calculations of molecular adsorption in several surface sites (i.e. hollow, bridge, top, on-top Au adatom and the novel staple motif) for different crystalline facets, i.e. Au(111) and (100). Langevin dynamics simulations have been performed to study the capping effects of alkanethiolates molecules on Au nanoparticles in the range 1-4 nm. The simulation results reveal an enhancement of the coverage degree whilst the nanoparticles diameter decreases. A high surface disorder due to the strong S-Au bond was found, in very good agreement with very recent experimental findings [M. M. Mariscal, J. A. Olmos-Asar, C. Gutierrez-Wing, A. Mayoral and M. J. Yacaman, Phys. Chem. Chem. Phys., 2010, 12, 11785]. © 2011 the Owner Societies.